Improving the efficiency of multisensory integration in older adults: audio-visual temporal discrimination training reduces the susceptibility to the sound-induced flash illusion. - Kenny, Rose; Newell, Fiona; Setti, Annalisa (My University, 2014)
From language to motor control, efficient integration of information from different sensory modalities is necessary for maintaining a coherent interaction with the environment. While a number of training studies have focused on training perceptual and cognitive function, only very few are specifically targeted at improving multisensory processing. Discrimination of temporal order or coincidence is a criterion used by the brain to determine whether cross-modal stimuli should be integrated or not. In this study we trained older adults to judge the temporal order of visual and auditory stimuli. We then tested whether the training had an effect in reducing susceptibility to a multisensory illusion, the sound induced flash illusion. Improvement in the temporal order judgement task was associated with a reduction in susceptibility to the illusion, particularly at longer Stimulus Onset Asynchronies, in line with a more efficient multisensory processing profile. The present findings set the ground for more broad training programs aimed at improving older adults׳ cognitive performance in domains in which efficient temporal integration across the senses is required.
PUBLISHED
Keywords: Multisensory perception; Audio-visual perception; Temporal order judgement; Cross-modal illusion; Ageing; Ageing; Neuroscience; Age related diseases; Behavioral/Experimental Psychology; Cognitive Development/Processes; Human genetics